Generic model for cooper pair splitting - Soller, Henning (International journal of modern physics. B, Condensed matter physics etc., 2014)
A superconductor connected to normal leads allows to generate Einstein-Podolsky-Rosen pairs by Cooper pair splitting (CPS). It has been realized with quantum dots either defined in carbon nanotubes or InAs nanowires. After establishing the presence of CPS in such devices new works have investigated the effects of a finite potential difference between the quantum dots to improve and characterize the efficiency of CPS. In this paper, we present a generic model for CPS and develop two minimal models specifically for the two experimental realizations and compare them to the experimental data. In addition, we also explore the relation of nonlocal charge transfer to positive current cross-correlation of currents and discuss the temperature dependence of CPS.